(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Skin diseases cause morbidity in major numbers of people around the world. Their pattern of distribution varies on certain factors like age, sex, occupation, genetics, environment etc. The aim of the study was to analyze and found prevalence of different skin diseases in this particular area of the country to provide useful findings. This study was carried out in the outdoor Department of Dermatology and Venereology of Southern Medical College Hospital, a tertiary teaching and referral hospital in Chittagong, Bangladesh from July 2011 to June 2015. There were 1644 patient, of them 637(38.75%) was male and 1007(61.25%) was female. Highest (26.03%) numbers of patient were in the age group of 21-30 years followed by 11-20 years age group (23.73%). Both male and female suffered mostly from same condition: eczematous disease (20.72% & 18.87%) followed by fungal infection(14.9% and 18.57%). Non-infectious skin disease was in 59.18% and infectious skin disease in 40.82%. Among non-infectious and infectious skin disease, eczematous disease and fungal skin disease were commonest, comprising 19.59% and 17.15% of the total patient respectively. Among the eczematous diseases, highest 38.5 % had eczema. Psoriasis comprises highest 48.1% among papulosquamous diseases. Regarding fungal skin diseases, 75.89% had dermatophyte infection and 65.42% were female. JCMCTA 2016 ; 27 (1) : 23 - 27